Studi Kelajuan Elektrolit Terhadap Kapasitas Baterai Dinamis Asam Timbal Sel Tunggal - Muhammad Ghufron; Istiroyah Istiroyah; Cholisina A. Perwita; Levinus Gobay; Fakhrusy Rizki Ramadhan; Kurriawan Budi Pranata (Universitas Sebelas Maret, 2020)
Abstract: Electrolyte flow rate is one of the important parameters on Redox Flow Battery (RFB) performance. A single cell lead acid battery has been made with the RFB system by giving 4 variations in flow speed (45 mL/min, 77 mL/min, 90 mL/min and 105 mL/min), two electrolyte concentrations (30% and 40%) and applied 1 A of charging-discharging current with the aim of an88ukmalyzing the relationship of the electrolyte flow rate of the battery to the RFB system capacity. The results showed that the flow of electrolytes from tanks outside the cell battery was able to increase battery capacity by increasing the number of spontaneous redox reactions during charging and discharging. The cycle time and battery capacity increase at the beginning of the filling-emptying cycle but have a downward trend with the increasing number of cycles. Batteries with an electrolyte concentration of 30% and speeds of 90 mL/mnt have the best performance in terms of discharging capacity compared to other batteries.Abstrak: Laju aliran elektrolit adalah salah satu parameter penting pada kinerja Redox Flow Battery (RFB). Baterai asam timbal sel tunggal telah dibuat dengan sistem RFB dengan memberikan 4 variasi kelajuan aliran (45 mL/mnt, 77 mL/mnt, 90 mL/mnt dan 105 mL/mnt), dua konsentrasi elektrolit (30% dan 40 %) dan diterapkan 1 A arus pengisian-pemakaian dengan tujuan menganalisis hubungan laju aliran elektrolit baterai dengan kapasitas sistem RFB. Hasil penelitian menunjukkan bahwa aliran elektrolit dari tangki di luar baterai sel mampu meningkatkan kapasitas baterai dengan meningkatkan jumlah reaksi redoks spontan selama pengisian dan pemakaian. Waktu siklus dan kapasitas baterai meningkat pada awal siklus pengisian-pengosongan tetapi memiliki tren menurun dengan meningkatnya jumlah siklus. Baterai dengan konsentrasi elektrolit 30% dan kelajuan 90 mL/mnt memiliki kinerja terbaik dalam hal kapasitas pemakaian dibandingkan baterai lainnya.